ショウワキチ シュウヘン ニ オケル ナンキョク ヒョウショウ ノ リュウドウ ソクテイ GPS ツウネン カンソク ノ ケッカ カラ - 新井, 直樹; アライ, ナオキ; 伊藤, 実; イトウ, ミノル; 土井, 浩一郎; ドイ, コウイチロウ; 青山, 雄一; アオヤマ, ユウイチ; Arai, Naoki; Ito, Minoru; Doi, Koichiro; Aoyama, Yuichi (2010)
P(論文) 第48次日本南極地域観測隊における越冬期間中に,昭和基地近傍の南極大陸氷床上において連続GPS観測を行い,約1年間の観測データを初めて取得した. 解析結果から得られた氷床の流動速度は,西北西の方向に5.1m/year, 14mm/dayであった. 観測期間中,測位点の速度はほぼ一定で,明らかな季節変動は認められなかった. We conducted GPS observations on the Antarctic ice sheet in the vicinity of Syowa Station, during wintering of the 48th Japanese Antarctic Research Expedition (JARE-48). Continuous GPS data for about one year was obtained for the first time. The flow velocity of the ice sheet, as determined by GPS analysis was 5.1m/year, or 14mm/day, and the direction was WNW. The movement of the ice sheet was fairly constant and no seasonal variations in velocity were observed. departmental bulletin paper